C/C–SiC composites derived from single‐source poly(silylene–acetylene) precursors. Issue 6 (6th July 2022) - Dong, Shilong; Hu, Xueying; Yuan, Qiaolong; Huang, Farong
Abstract: Carbon‐fiber‐reinforced carbon–silicon carbide (C/C–SiC) composites were prepared by impregnating carbon fibers with ethynylphenyl‐terminated poly(silylene–acetylene) (EPTSA) as a single‐source precursor with subsequent hot pressing and pyrolysis. The structural evolution, crystallization behavior, and graphitization of bulk C–SiC ceramics, as well as their mechanical properties and ablation behavior, were investigated. The EPTSA precursor starts to transform into inorganic SiC ceramic materials at 800°C, which is characterized by an amorphous structure with weight loss, shrinkage, and densification between 800 and 1000°C. The formation of SiC crystals inhibited the growth of the graphitic structure between 1000 and 1200°C. As the temperature was raised, both graphite and SiC crystals continued to grow, and the crystalline forms became more complete. The carbon‐fiber cloth (T300CF)‐reinforced C–SiC composite (T300CF/C–SiC) prepared using polymer infiltration and pyrolysis (PIP) exhibited excellent mechanical properties. After five PIP cycles, the flexural strength, flexural modulus, and interlaminar shear strength of the T300CF/C–SiC composite reached 169 MPa, 32.5 GPa, and 9.38 MPa, respectively. In addition, the chopped‐carbon‐fiber‐reinforced C–SiC composite fabricated using the PIP process demonstrated good oxyacetylene‐torch ablation properties. Abstract :